Queens in Folklores as Representation of Indonesian Feminism - Wiyatmi Wiyatmi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2023)
The view that the patriarchic system has dominated human life is untrue. Evidence has been found that, in the history of human civilization, women have been raised to the royal throne and ruled a kingdom. The existence of a queen has also been found in folklore in Indonesia. Using the qualitative research design with the perspectives of feminist literary criticism, the present study analyzes four folklore titles with a queen as the main character, such as: (1) The Legend of the Hermitage of Queen Kalinyamat, (2) Queen Kencanawungu, (3) Madam Undang Beautiful Queen from Kupang Island, and (4) The Legend of Princess Rengganis. Findings show no gender bias in the transfer of the royal inheritance or in choosing the successor of the royal throne in some kingdoms of regions in Indonesia. The crowning of a new ruler is more based on kinship and leadership qualities. This research also shows that before the emergence and development of feminism in the West, it has been existed in the archipelago, which can be called Indonesian feminism, i.e, feminism that gave women rights and voices not only in the domestic sphere but also in the public sphere, as a queen whose power was recognized.